Impact of Hurricane Katrina on the Coastal Systems of Southern Louisiana - Chuang, Wen-Ching; Eason, Tarsha; Garmestani, Ahjond; Roberts, Caleb (Frontiers in Environmental Science, 2019)
Natural disasters, such as hurricanes and forest fires, could trigger collapse and reorganization of social-ecological systems. In the face of external perturbations, a resilient system would have capacity to absorb impacts, adapt to change, learn, and if needed, reorganize within the same regime. Within this context, we ask how human and natural systems in Louisiana responded to Hurricane Katrina, and how the natural disaster altered the status of these systems. This paper discusses community resilience to natural hazards, and addresses the limitations for assessing disaster resilience. Furthermore, we assess social and environmental change of New Orleans and southern Louisiana spatially and temporally (i.e., pre- and post-Katrina). By analyzing changes in system conditions using social, economic and environmental factors, we identified some of the characteristics of the system’s reorganization trajectories. Although the ongoing population recovery may be a sign of revitalization, the city and metropolitan area continue to face socioeconomic inequalities and environmental vulnerability to natural disasters. The spatial distribution of social-ecological conditions over time reveals certain levels of change and reorganization after Katrina, but the reorganization did not translate into greater equity. Our analyses comprise three-time steps, including before and after the system was disturbed, and demonstrate an advanced approach for assessing disaster resilience.